Cryphonectria parasitica, the causal agent of chestnut blight: invasion history, population biology and disease control. (24th April 2017) - Rigling, Daniel; Prospero, Simone
Summary: Chestnut blight, caused by Cryphonectria parasitica, is a devastating disease infecting American and European chestnut trees. The pathogen is native to East Asia and was spread to other continents via infected chestnut plants. This review summarizes the current state of research on this pathogen with a special emphasis on its interaction with a hyperparasitic mycovirus that acts as a biological control agent of chestnut blight. Taxonomy: Cryphonectria parasitica (Murr.) Barr. is a Sordariomycete (ascomycete) fungus in the family Cryphonectriaceae (Order Diaporthales). Closely related species that can also be found on chestnut include Cryphonectria radicalis, Cryphonectria naterciae and Cryphonectria japonica . Host range: Major hosts are species in the genus Castanea (Family Fagaceae), particularly the American chestnut ( C. dentata ), the European chestnut ( C. sativa ), the Chinese chestnut ( C. mollissima ) and the Japanese chestnut ( C. crenata ). Minor incidental hosts include oaks ( Quercus spp.), maples ( Acer spp.), European hornbeam ( Carpinus betulus ) and American chinkapin ( Castanea pumila ). Disease symptoms: Cryphonectria parasitica causes perennial necrotic lesions (so‐called cankers) on the bark of stems and branches of susceptible host trees, eventually leading to wilting of the plant part distal to the infection. Chestnut blight cankers are characterized by the presence of mycelial fans and fruiting bodies of the pathogen. Below the canker the tree may react by producing epicormic shoots. Non‐lethal, superficial or callusing cankers on susceptible host trees are usually associated with mycovirus‐induced hypovirulence. Disease control: After the introduction of C. parasitica into a new area, eradication efforts by cutting and burning the infected plants/trees have mostly failed. In Europe, the mycovirus Cryphonectria hypovirus 1 (CHV‐1) acts as a successful biological control agent of chestnut blight by causing so‐called hypovirulence. CHV‐1 infects C. parasitica and reduces its parasitic growth and sporulation capacity. Individual cankers can be therapeutically treated with hypovirus‐infected C. parasitica strains. The hypovirus may subsequently spread to untreated cankers and become established in the C. parasitica population. Hypovirulence is present in many chestnut‐growing regions of Europe, either resulting naturally or after biological control treatments. In North America, disease management of chestnut blight is mainly focused on breeding with the goal to backcross the Chinese chestnut's blight resistance into the American chestnut genome.